The Practice of Enterprise Modeling 5th IFIP WG 8.1 Working Conference, PoEM 2012, Rostock, Germany, November 7-8, 2012. Proceedings - Sandkuhl, Kurt.; Seigerroth, Ulf.; Stirna, Janis; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This volume constitutes the proceedings of the 5th IFIP WG 8.1 Working Conference on the Practice of Enterprise Modeling, held in Rostock, Germany, during November 7-8, 2012. The focus of the PoEM conference series is on improving the understanding of the practice of enterprise modeling by offering a forum for sharing experiences and knowledge between the academic community and practitioners from industry and the public sector. The 15 papers presented were carefully reviewed and selected from 45 submissions, and reflect different facets of enterprise modeling, including organizational and social issues as well as methodological and technical aspects. The papers are organized in five thematic sessions on enterprise modeling, business modeling, process modeling, enterprise architecture, and model-driven development.
Enterprise Modeling -- Process Modeling -- Business Modeling -- Enterprise Architecture and Enterprise Modeling -- Model-Driven Development.
Keywords: Economics; Information systems; Management information systems; Economics/Management Science; Business Information Systems; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl. Internet).